IDENTIFIKASI MISKONSEPSI MATERI SEL PADA PESERTA DIDIK DI KELAS XI IPA MAN 2 KOTA PADANG - Noviandra Syarif; Heffi Alberida; Rahmadhani Fitri; Relsas Yogica (Bioilmi: Jurnal Pendidikan, 2023)
Cell material is one of the biological materials that contains many abstract concepts and objects, this causes students to have difficulty understanding the concept and has an impact on the low learning outcomes of students. Misconceptions arise when learners develop their own understanding of a concept, but the concept is wrong and different from the actual concept. Therefore, it is necessary to identify the level of understanding of the concept of students. Identification is done using a Multiple Choice test with CRI which aims to determine the percentage level of understanding of students on cell material. Students' understanding is categorized into understanding the concept, misconceptions and not understanding the concept. The results showed that the percentage of students' misconceptions on cell organelles was 34.03%, the concept of differences between animal cells and plant cells was 31.48%, the concept of cell types was 28.47%, the concept of cell components was 35.42% and the concept of cell bioprocessing was 36.11%. The average misconception of students on cell material is 33.10%. The average percentage of students' misconceptions is classified as low.